Ensaio fílmico, eterno devir: projeto de filme inacabado e de um cinema futuro - Almeida, Gabriela Machado Ramos de (2018)
This paper presents a theoretical discussion about the constitution of a field of studies for the essay film. This research identifies a becoming-essay in both practice and theory of cinema since the 1940s. I also propose a mapping of recent and relevant studies which support the effective constitution of the film essay as an autonomous form or the "fourth domain of cinema" (Teixeira, 2015). Finally, I present a notion of film essay that dialogues with the contributions of authors such as Català (2005 and 2014) and Corrigan (2015).